A scoping review of the unmet needs of patients diagnosed with idiopathic pulmonary fibrosis (IPF) - Eustace-Cook, Jessica; Brady, Anne-Marie; Bramhill, Carita (My University, 2024)
Aims: Patients diagnosed with idiopathic pulmonary fibrosis (IPF) have a high symptom burden and numerous needs that remain largely unaddressed despite advances in available treatment options. There is a need to comprehensively identify patients’ needs and create opportunities to address them. This scoping review aimed to synthesise the available evidence and identify gaps in the literature regarding the unmet needs of patients diagnosed with IPF. Methods: The protocol for the review was registered with Open Science Framework (DOI 10.17605/OSF.IO/SY4KM). A systematic search was performed in March 2022, in CINAHL, MEDLINE, Embase, PsychInfo, Web of Science Core Collection and ASSIA Applied Social Science Index. A comprehensive review of grey literature was also completed. Inclusion criteria included patients diagnosed with IPF and date range 2011–2022. A range of review types were included. Data was extracted using a data extraction form. Data was analysed using descriptive and thematic analysis. A total of 884 citations were reviewed. Ethical approval was not required. Results: 52 citations were selected for final inclusion. Five themes were identified: 1.) psychological impact of an IPF diagnosis. 2.) adequate information and education: at the right time and in the right way. 3.) high symptom burden support needs. 4.) referral to palliative care and advance care planning (ACP). 5.) health service provision-a systems approach.
PUBLISHED
Keywords: idiopathic pulmonary fibrosis (IPF); scoping review; high symptom burden; idiopathic pulmonary fibrosis (IPF); scoping review; high symptom burden